Effect of cognitive reappraisal on archery performance of elite athletes: The mediating effects of sport-confidence and attention - Wang, D.; Hu, T.; Luo, R.; Shen, Q.; Wang, Y.; Li, X.; Qiao, J.; Zhu, L.; Cui, L.; Yin, H. (Frontiers in Psychology, 2022)
Through empirical studies or laboratory tests, previous studies have shown that sport-confidence, attention, and emotion regulation are key factors in archery performance. The present study aims to further identify the effects and pathways of sport-confidence, attention, and cognitive reappraisal (a specific emotion regulation strategy) on real-world archery performance by constructing a hypothesized model to provide a basis for scientific training of athletes to improve sport performance. A survey design was utilized on a sample of 61 athletes (12 international-level athletes, 30 national-level athletes, and 19 first-class athletes) from the Chinese National Archery Team to test the model. The measurement and hypothesized models were tested using partial least squares structural equation modeling (PLS-SEM). The results indicate that the model fit well and explained 33.6% of the variance in archery performance. Sport-confidence (total effects = 0.574, p < 0.001) and attention (total effects = 0.344, p = 0.009) were important predictive indicators of archery performance, while the relationship between cognitive reappraisal and archery performance showed considerable complexity (direct effects = -0.268, p = 0.020; total effects = -0.007, p = 0.964). We conclude that the development of sport-confidence and attention of archery athletes should be strengthened, but athletes who use cognitive reappraisal in archery competition should be mindful of its potential appropriation of cognitive resources and should be directed to improve sport-confidence or develop a positive orientation to arouse excitement.